1993
DOI: 10.1144/gsl.sp.1993.074.01.30
|View full text |Cite
|
Sign up to set email alerts
|

Extensional tectonics in the Himalayan orogen, Zanskar, NW India

Abstract: Large-scale nappes of the deformed Higher Himalayan Crystallines (HHC) were thrust southward over the Lesser Himalayan Proterozoic foreland during the Late Cenozoic. Critical evaluation of shear fabrics, reveals that the HHC underwent an earlier phase of ductile shearing with top-to-southwest overthrust-type sense of movement. On which was superposed layer-parallel NE-trending extension. As a consequence, the Zanskar Shear Zone (ZSZ) along the northern boundary of the HHC is re-interpreted as a complex ductile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 28 publications
6
41
0
Order By: Relevance
“…This event was likely coeval with the SW directed nappe tectonics (e.g., Nyimaling-Tsarap nappe) responsible for the middle Eocene low-grade metamorphism in the Tethyan Himalaya constrained by 40 Ar/ 39 Ar white mica ages (circa 45 -42 Ma [Bonhomme and Garzanti, 1991;Wiesmayr and Grasemann, 1999;Schlup et al, 2003]). This interpretation is consistent with the observations by Patel et al [1993] that the extensional ZSZ reactivates a former thrust.…”
Section: Previous Age Constraintssupporting
confidence: 93%
See 1 more Smart Citation
“…This event was likely coeval with the SW directed nappe tectonics (e.g., Nyimaling-Tsarap nappe) responsible for the middle Eocene low-grade metamorphism in the Tethyan Himalaya constrained by 40 Ar/ 39 Ar white mica ages (circa 45 -42 Ma [Bonhomme and Garzanti, 1991;Wiesmayr and Grasemann, 1999;Schlup et al, 2003]). This interpretation is consistent with the observations by Patel et al [1993] that the extensional ZSZ reactivates a former thrust.…”
Section: Previous Age Constraintssupporting
confidence: 93%
“…BT, Baralacha La Thrust; DTFZ, Dutung-Thaktote Fault Zone; HHCZ, High Himalayan Crystalline Zone; JD, Jahla Detachment; KSZ, Khanjar Shear Zone; LHC, Lesser Himalayan Crystalline; LT, Lagudarsi La Thrust; MBT, Main Boundary Thrust; MCT, Main Central Thrust; MTZ, Miyar Thrust; PT, Parang Thrust; SD, Sangla Detachment; SF, Sarchu Fault; ZSZ, Zanskar Shear Zone. a consequence, the tectonometamorphic evolution of this part of the range is well constrained [e.g., Honegger et al, 1982;Kündig, 1989;Stäubli, 1989;Patel et al, 1993;Dèzes, 1999;Searle et al, 1999;Walker et al, 1999;Stephenson et al, 2000;Epard and Steck, 2004]. In contrast, the timing of the metamorphic and tectonic evolution of the southern limb of the Gianbul dome is still poorly constrained.…”
Section: Introductionmentioning
confidence: 99%
“…Although known geologic relationships support this interpretation, other aspects of the complex are also consistent with the possibility that it may have rooted along the South Tibetan Fault System as a remnant of early south-verging thrusting that pre-dated recent north-verging normal movement associated with gravitational collapse [29]. The metamorphic grade associated with the structurally lowest levels of the complex is similar to that found within the southernmost parts of the Tethyan zone adjacent to the GH and the South Tibetan Fault System.…”
Section: Resultssupporting
confidence: 52%
“…Additionally, relatively un-deformed Silurian strata in the Himalaya are preserved only in the TH; they are absent in the LH, where Permian strata rest directly on the Lower Cambrian. Middle Cambrian to Lower Permian strata are also cut-out below a Permian unconformity south of the extension of the MCT (the P^K fault) in Pakistan, whereas to the north of the fault a full pre-Permian Tethyan succession exists [29]. Whether the Kathmandu Complex represents (1) a part of the GH that roots back to the MCT and escaped strong metamorphism, or (2) a part of the TH that moved along the STDS, remains an unresolved problem.…”
Section: Resultsmentioning
confidence: 99%
“…d A schematic cross-section of the Zanskar Shear Zone along the NE-SW geographic direction. The structures reported by Patel et al (1993) are shown: 1 top-to-SW sense of ductile shearing, 3 top-to-NE (down) extensional ductile shearing, 1 0 Top-to-SW sense of brittle shearing represented by duplexes, and 2 0 Northeasterly steeply dipping brittle faulting. Ductile shearing represented by 1 and 3 are subsequently referred as 'shearing-1' and 'shearing-3', respectively.…”
Section: Introductionmentioning
confidence: 99%